Calorimetry of amorphous calcium carbonate is correlated with its lithification and durability as synthetic stone—implications for CO2 storage and utilization - Levey, Catherine; Reed, Jillian; Sanchez, Christopher; Schneider, Jacob; Constantz, Brent R. (Frontiers in Materials, 2024)
The properties of amorphous calcium carbonate (ACC) and its transformations to crystalline polymorphs are frequently studied in aqueous systems and in small quantities. In this study, synthetic calcium carbonate stones are created from bulk ACC and crystalline polymorphs, which were precipitated from gaseous CO2, at a gradient of end pH. Some of the ACCs hardened into stones which are durable against an abrasion and impact test, while some of the ACCs create fragile, friable stones. When ACCs which transform to durable stones and those which transform into fragile stones were subject to calorimetry, significant differences were observed. These stones, synthesized from gaseous CO2, can be used as a storage reservoir for utilized CO2 in construction and other infrastructure applications.